Socialization of Youth Nutrition Information in Prevention of Anemia - Justina Purwarini; Tuti Asrianti Utami (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The behavior of human consumption of food is determined by human life behaviour in the adolescent period. This makes adolescents the target of nutritional intervention with the aim of improving health status. Changes in psychology, physiology, social change, knowledge and misnutrition behavior in adolescents will lead to nutritional problems. One of the causes of anemia is a lack of nutritional foods such as animal proteins, green vegetables and other foods that are a source of iron. A good diet and a balanced diet will affect the nutritional requirements of the body so that the occurrence of anemia can be overcome. The aim of this community service is to raise awareness of nutrition and balanced nutrition issues in early adolescent groups. It can be measured by the results of the questionnaire given at the end of the activity. The participants who participated in this counseling were 7th grade Yunior High School students at SMPN 28 Jakarta with a total of 61 students. The study was successful because the results showed an increase in the knowledge of the participants.